Nonlinear feedback control of axisymmetric aerial vehicles. (March 2015) - Pucci, Daniele; Hamel, Tarek; Morin, Pascal; Samson, Claude
Abstract: We investigate the use of simple aerodynamic models for the feedback control of underactuated aerial vehicles flying with large flight envelopes. Thrust-propelled vehicles with a body shape symmetric with respect to the thrust axis are considered. Upon a condition on the aerodynamic characteristics of the vehicle, we show that the equilibrium orientation can be explicitly determined as a function of the desired flight velocity. This allows for the adaptation of previously proposed control design approaches based on the thrust direction control paradigm. Simulation results conducted by using measured aerodynamic characteristics of quasi-axisymmetric bodies illustrate the soundness of the proposed approach.